Trade and Global Market - Bobek, Vito (IntechOpen, 2018)
International capital flows have become significantly important since the increasing trend in globalization of the early 1990s. The diversified global market has become one single market, the investment sector has strengthened itself and countries have started to allow investment inflows for economic growth. Empirical studies have revealed that political instability, political regimes and the quality of existing institutions, in addition to the transition procedure of a nation itself, have a deterministic effect on the linkage of economic growth and corruption. Additionally, exchange rate volatility can determine the amount of exchange rate risk that firms can be opposed to; therefore, exchange rate volatility is a crucial issue that should be monitored by central banks to prevent contagion of negative microeconomic developments to macroeconomic activity and stability. The significant transformation of banking markets raises many questions regarding the motives of financial organisations to finance SMEs, for example what are the factors that have an impact on these organisations' choice and market strategies?